2018
DOI: 10.4103/0366-6999.226069
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-Induced Cerebral Small Vessel Disease Leading to Cognitive Impairment

Abstract: Objective:Alzheimer's disease and vascular dementia are responsible for more than 80% of dementia cases. These two conditions share common risk factors including hypertension. Cerebral small vessel disease (CSVD) is strongly associated with both hypertension and cognitive impairment. In this review, we identify the pathophysiological changes in CSVD that are caused by hypertension and further explore the relationship between CSVD and cognitive impairment.Data Sources:We searched and scanned the PubMed database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 56 publications
6
44
1
3
Order By: Relevance
“…These people contributed to 29-49% of the multimorbidity clusters at the 6-year follow-up and to 16-50% of the multimorbidity clusters at 12 years, especially to those characterized by cardiovascular, eye, respiratory, and musculoskeletal diseases. Despite it is now well established that cardiometabolic conditions such as diabetes, obesity, dyslipidemia, and hypertension are important risk factors for the development of several cardiovascular diseases, less is known about the same risk factors, and the risk of other chronic conditions 26,27 . A few individuals moved from a specific cluster to the unspecific cluster over time.…”
Section: Discussionmentioning
confidence: 99%
“…These people contributed to 29-49% of the multimorbidity clusters at the 6-year follow-up and to 16-50% of the multimorbidity clusters at 12 years, especially to those characterized by cardiovascular, eye, respiratory, and musculoskeletal diseases. Despite it is now well established that cardiometabolic conditions such as diabetes, obesity, dyslipidemia, and hypertension are important risk factors for the development of several cardiovascular diseases, less is known about the same risk factors, and the risk of other chronic conditions 26,27 . A few individuals moved from a specific cluster to the unspecific cluster over time.…”
Section: Discussionmentioning
confidence: 99%
“…3 Periventricular and deep WMHs have been associated with different etiologies; periventricular WMH is due to hemodynamic insufficiency (hypoperfusion), 2,[4][5][6][7] whereas deep WMH is due to small vessel diseases. 2,[8][9][10] Hypertension can cause both cerebral hypoperfusion [11][12][13] and small vessel disease 14,15 and has been associated with the presence and amount of both periventricular WMH 16,17 and deep WMH. 18,19 In hypertension, cerebral hypoperfusion is known to result from the increased vascular resistance and disturbed hemodynamic flow patterns, [11][12][13]20,21 whereas the small vessel disease results from endothelial dysfunction of the blood-brain barrier.…”
Section: Association Of Low Blood Pressure With White Matter Hyperintmentioning
confidence: 99%
“…Similarly, the somatosensory system is reported to decline in healthy aging (Heft and Robinson, 2017;Strömmer et al, 2017) though somatosensory processing and its association with cognitive aging has not been extensively studied. Though generalized explanations specific to sensory integrity as described above have been influential in the aging literature, they also neglect other biological factors of aging which are related to cognition, including vascular hypertension-related changes (Liu et al, 2018). Furthermore, few studies have considered the contribution or confounds of long term blood pressure medication or the increasing evidence that cerebral small blood vessel disease (CSVD) is emerging as a principal risk factor for cognitive impairment in apparently healthy adults (Liu et al, 2018;Jiménez-Balado et al, 2019).…”
Section: The Association Between Perceptual Abilities and Decline In mentioning
confidence: 99%
“…Indeed, hypertension is a risk factor for CSVD and neuroinflammation (Allison and Ditor, 2014;Chen et al, 2016), and in turn, cognitive decline. The link between characteristics of CSVD and cognitive decline has been reviewed in a recent study conducted by Liu et al (2018) who explored hypertensive vasculopathy factors including small vascular lesions, inflammatory reactions, hypoperfusion, and blood-brain barrier damage. They found that all factors associated with hypertension are vital prognostic indicators of the development of cognitive impairment, particularly when blood pressure management is poor (Liu et al, 2018).…”
Section: Theory/hypothesismentioning
confidence: 99%